METODE PELAKSANAAN, EFISIENSI BIAYA DAN WAKTU PEKERJAAN GALIAN BATU DENGAN METODE PELEDAKAN (BLASTING) PADA PROYEK JALAN TOL SIGLI – BANDA ACEH SEKSI 1A - Danu Nugraha; Sihombing, Alexander Tuahta; Nasution, Mahliza (Jurnal Bidang Aplikasi Teknik Sipil dan Sains (BATAS), 2025)
The Sigli - Banda Aceh Toll Road is the first toll road in Aceh province, stretching 74.2 kilometers (km) and consisting of 6 sections. Rock excavation work includes excavation of rock chunks with a volume of 1m3 or more and all rocks or other materials whose excavation requires air pressure tools or drilling, and blasting according to the instructions of the Work Director. This study aims to determine the stages or methods of rock excavation work using the blasting method and to analyze costs based on the Powder Factor (PF) value and the time required to complete the rock excavation work. Based on the results of the study, the stages of rock excavation work using the blasting method begin with the construction of an explosives warehouse, preparation for drilling blast holes, drilling, mobilization of explosives, filling blast holes with explosives (charging), blocking blast holes (stemming), connecting the blasting series (tie up), preparation before blasting, blasting and post-blasting checks. Blasting geometry applied to the rock excavation work in the Sigli – Banda Aceh Toll Road Project Section 1A Sta 15+350 – Sta 15+750 includes the following for the Initial Geometry Plan: Hole Diameter (D) 3.5 inches, Burden (B) 2.5 m, Spacing (S) 3 m, Height of the Stage (H) 6 m, Explosives 30 Kg, and PF 0.67. Geometry Realization: Hole Diameter (D) 3.5 inches, Burden (B) 2.5 m, Spacing (S) 3 m, Height of the Stage (H) 6 m, Explosives 30 Kg, and PF 0.67. Expand Geometry: Hole Diameter (D) 3.5 inches, Burden (B) 3 m, Spacing (S) 3.5 m, Height of the Stage (H) 6 m, Explosives 30 Kg, and PF 0.48. The Powder Factor (PF) value in the blasting geometry design obtained a PF value exceeding 0.3 kg/m3 which means it is not economical, the economical PF value ranges from 0.20 - 0.30 kg/m3. Economical Geometry Design is obtained by "trial and error" or rule of thumb according to the limits of ICI Explosives with the results: Hole Diameter (D) 3.5 inches, Burden (B) 3.5 m, Spacing (S) 5 m, Height of Tier (H) 6 m, Explosives 30 Kg, and PF 0.29. The time required to complete the rock excavation work on the Sigli - Banda Aceh Toll Road Project Section 1a Sta 15 + 350 - Sta 15 + 750 with the initial planned geometry design takes 3.77 months at a cost of Rp. 40,336,928,850.00 while with an efficient geometric design it takes 1.62 months with a cost of Rp. 39,678,466,850.00.